The Influence Of Organizational Culture And Training On The Performance Of National Social Security Agency for Employment - Peni Eriyati; N. Neni Triana; Thomas Nadeak (PT. Berkah Digital Teknologi, 2024)
Purpose of the study — This study aims to explain the influence of Organizational Culture and training on employee performance, both simultaneously and partially Research method—The research employs quantitative methods, using a saturated sampling technique that includes all 31 employees of the Karawang Employment BPJS as the sample. Result— The findings indicate that both organizational culture and training significantly affect employee performance, with a significance value (sig.F) of 0.000. Additionally, organizational culture shows a significant partial effect on employee performance. Conclusion— The analysis, conducted through multiple linear regression using t-tests and f-tests, confirms that organizational culture and training are crucial factors influencing employee performance.